A PÉCORA, DE NATÁLIA CORREIA: DRAMATURGIA, HISTÓRIA E RELIGIÃO - SANTOS, GIOVANA DE PAULA (2023)
The present research intends to analyze, in the light of theoretical conceptions about dramaturgy, History, and religion the play A Pécora (1990) by Natália Correia, seeking to identify the representation of the two faces of Melania Sabini, demystifying the character who acts as a saint and a prostitute, punctuating the relationship that is established between reality and imagination. Natália Correia’s work revisits History and stages a fictional variation of the Apparitions of Fátima, reinterpreting new contours of the Miracle of the Sun, providing, through Literature, the split between the archetype of a sanctified figure. For this purpose, the teachings of Bertold Brecht (1978), Luciana Stegagno Picchio in Story of theater português (1964), Brief Story of Portugal (2016) by António H. Rodrigo de Oliveira Marques, Myth and reality (1972) and The sacred the profane (1992) by Mircea Eliade, among other researchers, will serve as references. In this way, we will intend to reflect how the writing of female authorship, specially Natália Correa, proposes a new perspective at the liberation of the female body and thought, intertwining the collective voices that support the miracle and the fictitious occupation of the gaps left in this event, seeking, through the broadening of horizons that theatrical art makes possible, the socio-historical and cultural critical analysis present in the play. Finally, it is also important for us to verify how the relation of discourses, when played on stage in front of the public, are able to show that the past is present, even in the actual moment.